Nguồn hình thành trữ lượng nước dưới đất vùng lưu vực sông Sài Gòn - Chân, Ngô Đức; Kỳ, Nguyễn Việt (Vietnam Journal of Earth Sciences, 2012)
summaryOriginating source of groundwater reserve in Saigon river basinOriginating source of groundwater reserve is not only one of research speciality in hydrogeology, but also an important information for groundwater resources exploitation management and protection.Commonly, its calculation is complicated, especially in areas of complex hydrogeological conditions such as Saigon river basin. Therefore, this problem has not been studied yet so far. For the first time, groundwater system was studied in details for Saigon river basin by quantitative calculation of originating sources of groundwater reserve based on solutions of the existing groundwater flow model ([4]). Besides, via solutions of groundwater balance issue, horizontal salinity intrusion under influence of groundwater exploitation was also calculated for 4 potential aquifers.